Importance of Intermittent Cardiotocographic Monitoring Prior to Misoprostol-Assisted Induction of Labour - Nidda Yaseen, Uzma Saleem, Sarah Hafeez, Yasmin Fatima, Umbreen Akram, Tayyaba Rashid (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the importance of intermittent cardiotocographic monitoring during misoprostol-assisted induction of labour in pregnancies lasting weeks or more. Methods: This descriptive study was carried out in the Obstetrics and Gynecology department of Combined Military Hospital, Kharian Cantt for the duration from January 2022 to August 2022 among 130 primigravida patients underwent CTG before receiving transvaginal dose of misoprostol. Neonatal admissions, the mode of delivery, the Apgar score, and indications of induction were the variables examined. Results: Forty-two (70%) of the C-section patients had reassuring CTG and significantly low Apgar scores at 1 minute. Seven (8.5%) of the patients with thick meconium had non-reassuring CTG. Twelve neonates (9.2%) in total required resuscitation, 9 (75%) of whom had reassuring CTGs while 3(25%) had non-reassuring CTGs. The overall admission rate in NICU was 10%, and 38.5% of neonates that required resuscitation had non-reassuring CTG. Neonatal mortality was nil during the study time. Conclusions: Patients who had their labour induced with misoprostol had non-reassuring CTG among 50% of cases and had thick meconium stained liquor. Therefore, we can lower neonatal morbidity and mortality by early foetal impairment detection. Neonatal mortality was nil during the study time. Keywords: cardiotocography, induction, resuscitation, Apgar score and caesarean section